Embedding key strategies from the Incredible Years Teacher Programme within teacher practice, over time (Kairaranga, 2023)
There is considerable evidence supporting the success of the Incredible Years Teacher (IYT) Programme. Despite this, few studies in Aotearoa New Zealand have investigated teachers’ ongoing use of IYT strategies once they have completed their training. This research examined whether teachers felt they had embedded the use of IYT strategies in their practice post their initial IYT training, and whether they used some IYT strategies more frequently than others. Using a mixed methods approach, this research surveyed 65 teachers who trained 2-10 years ago in Ōtautahi. The results indicate that teachers feel confident implementing IYT strategies within their practice, and they implement strategies from the lower layers of the IYT pyramid more frequently than more intrusive strategies from the upper layers. Teachers also reported that training with colleagues and working within schools that embraced IYT helped them embed their learning in their practice. This research has implications for IYT group leaders, peer coaches, and administrators, as well as principals and their leadership teams, RTLB Cluster Managers, Ministry of Education coordinators, and classroom teachers who are considering training. Overall, the results indicate that teachers benefit from IYT training and continue to implement key IYT strategies in their practice after they have completed their training.